2012
DOI: 10.1111/j.1600-0625.2011.01422.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neurons from adult human skin‐derived precursors in serum‐free medium : a PCR array and immunocytological analysis

Abstract: Adult stem cells could be small sources of neurons or other cellular types for regenerative medicine and tissue engineering. Recently, pluripotent stem cells have been extracted from skin tissue, which opened a new accessible source for research. To routinely obtain a high yield of functional neurons from adult human skin stem cells with defined serum-free medium, stem cells from abdominal skin were cultured in serum-free medium. To differentiate them, we used a defined medium containing growth factors. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Neuronal differentiation is achieved using AMPc and a cocktail of neurotrophins such as BDNF, NT-3 and NGF while glial differentiation into Schwann cell is promoted by the addition of forskolin and heregulin 1 to the culture medium(267)(268)(269)(270) (Figure 6). Little is known regarding the role of SKPs in skin wound healing or a potential involvement in sensory nerve regrowth but several studies have shown that SKP-derived Schwann cells help promoting sciatic nerve regeneration in rodents(271)(272)(273).…”
mentioning
confidence: 99%
“…Neuronal differentiation is achieved using AMPc and a cocktail of neurotrophins such as BDNF, NT-3 and NGF while glial differentiation into Schwann cell is promoted by the addition of forskolin and heregulin 1 to the culture medium(267)(268)(269)(270) (Figure 6). Little is known regarding the role of SKPs in skin wound healing or a potential involvement in sensory nerve regrowth but several studies have shown that SKP-derived Schwann cells help promoting sciatic nerve regeneration in rodents(271)(272)(273).…”
mentioning
confidence: 99%
“…Strategies using neuropeptides to stimulate skin cells and trophic factors to stimulate neurite growth can be either combined or provided sequentially. A possible source of human neuropeptides, ideally from sensory neurones, could be generated using skin‐derived precursors (SKPs) or induced pluripotent stem cells (iPS) differentiated into neurones . Due to the distinct role of different neuropeptides and NTs, the use of a cocktail would be interesting with delivery either by single administration or ideally by delayed delivery into the wound .…”
Section: Therapeutic Strategies To Improve Wound Healing and Reinnervmentioning
confidence: 99%
“…In addition, tumorigenicity of ES cells and iPS cells is another concern in application to cell therapy. Recent studies have elucidated the existence of a particular type of stem cells such as skin-derived precursors (SKPs) in the adult human dermis, which exhibit the similar properties to neural crest cells (Gingras 2007;Joannides 2004;Lebonvallet 2012). SKPs are reported to be able to differentiate into Schwann cells within a week in a high rate in vitro (>95%) (McKenzie 2006), suggesting that SKPs will be a good candidate as a source for Schwann cell generation.…”
Section: Introductionmentioning
confidence: 98%